AN EXPLORATION OF WEST SUMBA SENIOR HIGH SCHOOL STUDENTS’ READING INTERESTS, HABITS, AND DIFFICULTIES - Setiamunadi, Antonina Anggraini (IJIET (International Journal of Indonesian Education and Teaching), 2026)
Reading is important for students to enrich knowledge and collect important information useful not only for their academic life but also for their social, economic, and civic life. A good reading habit can be initiated by engaging students with reading materials which arouse their interests. Even if students have good interests and habits in reading, they may face difficulties in reading which may decrease their reading interests and habits. In rural areas in Indonesia, there are many obstacles affecting students’ reading interests and habits. The objective of this study is to investigate English reading interests, habits, and difficulties of West Sumba senior high school students. This study uses a descriptive quantitative approach with a survey design. The results of this study showed that the students have a good interest in reading Indonesian and English texts, and they have a quite good reading habit even though the texts that they read on a daily basis in Indonesian language cannot be categorized as appropriate reading materials. The common difficulties faced by the students in their reading activities are unsupportive parents and teachers, lack of English reading sources, and their preference to watch TV or play with their gadgets rather than to read.